APPLYING BLOOM’S TAXONOMY IN NEUROSCIENCE: A PRACTICAL EXAMPLES - Karkera, Shilpa; Manahan, Kelly; Lakhani, Bhavesh (International Journal of Research -GRANTHAALAYAH, 2024)
Bloom's Taxonomy serves as a structured framework in neuroscience education, guiding educators in designing, implementing, and assessing learning objectives across various cognitive levels. This abstract explores the practical application of Bloom's Taxonomy in teaching neuroscience concepts, offering insights into effective student engagement. In neuroscience education, Bloom's Taxonomy is invaluable for curriculum development, instructional strategies, and assessment methods. At the foundational "remembering" level, students recall neuroanatomical structures, physiological processes, or terminology. For example, they identify brain regions or recall neurotransmitter functions. Progressing to the "understanding" level, students comprehend neuroscientific principles. This entails explaining action potential propagation or neural pathways in sensory perception. Educators use case studies, discussions, or multimedia for deeper understanding. At the "applying" level, students apply neuroscience knowledge to solve real-world problems. They analyze clinical cases and propose interventions based on neuroanatomy and physiology understanding. "Analyzing" prompts critical evaluation of neuroscience theories or research. This involves literature reviews, study critiques, or experiment design. Finally, at the highest level of "creating," students are challenged to synthesize their understanding of neuroscience concepts to generate novel ideas, designs, or solutions. This could entail developing research proposals, designing educational materials, or proposing innovative treatments for neurological disorders.